2008
DOI: 10.1128/jb.01388-07
|View full text |Cite
|
Sign up to set email alerts
|

The Leucine-Responsive Regulatory Protein, Lrp, Activates Transcription of thefimOperon inSalmonella entericaSerovar Typhimurium via thefimZRegulatory Gene

Abstract: The fim operon of Salmonella enterica serovar Typhimurium encodes type 1 fimbriae. The expression of fim is controlled in response to environmental signals through a complex regulatory cascade involving the proteins FimW, FimY, and FimZ and a genetic locus, fimU, that encodes a rare arginine tRNA. We discovered that a knockout mutation in lrp, the gene that codes for the leucine-responsive regulatory protein (Lrp), inhibited fim transcription. The loss of fim gene expression was accompanied by a corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 81 publications
4
53
1
Order By: Relevance
“…An H-NS and Lrp regulatory switch drives tos operon transcriptional regulation. It has been previously proposed and noted that Lrp might act to anti-silence H-NS repression (35,38,59,68). We hypothesize, therefore, that an H-NS and Lrp regulation switch (i.e., predominance of either H-NS or Lrp) explains the observed regulation of the tos operon.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…An H-NS and Lrp regulatory switch drives tos operon transcriptional regulation. It has been previously proposed and noted that Lrp might act to anti-silence H-NS repression (35,38,59,68). We hypothesize, therefore, that an H-NS and Lrp regulation switch (i.e., predominance of either H-NS or Lrp) explains the observed regulation of the tos operon.…”
Section: Resultsmentioning
confidence: 78%
“…In agreement with this, others have noted the possibility that Lrp and H-NS antagonize the activity of each other or could interact together to potentiate gene regulation (35,38,59,68). This type of regulation resembles a regulatory switch, in which one nucleoid-structuring protein switches in predominance at key regulatory elements to perturb gene regulation.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Rao and colleagues (75) suggested that type 1 fimbrial expression is controlled by a positive feedback loop involving FimY and FimZ as well as a negative feedback loop between FimW and FimY. In addition, the expression of fimZ itself has been shown to be controlled at the level of transcription by Lrp, and Lrp-negative mutants show no fim expression (59). Lrp binds to a region upstream (between bp 65 and 170) of the fimZ transcription start site and is proposed to facilitate fimZ expression, leading to increased type 1 fimbrial production due to activation by FimZ.…”
Section: Additional Dna Binding Fimbrial Regulatorsmentioning
confidence: 99%